Konsumsi Energi Konversi Sepeda Motor Listrik Dengan Fixed Belt Transmission Pada Kecepatan 30 km/jam - Alward, Jay Athar Van; Widiyarta, I Made; Darma, I Wayan Arya; Widhiada, I Wayan; Tista, Si Putu Gede Gunawan; Astika, I Made (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract Indonesia has massive number of conventional motorcycles, totaling 125 million units in 2022, therefore, the electrification of motorized vehicles is pursued as the best alternative to address the massive number of conventional motorcycles in Indonesia. Conventional motorcycles converted into electric motorcycles are powered by batteries, the primary challenge with battery usage is the limited travel range and relatively long charging times. This issue can be mitigated by using the appropriate transmission ratio, influencing the amount of energy consumed. Some studies suggest that the smaller the transmission ratio, the less energy is consumed. Research was conducted using a modified transmission (Fixed Belt Transmission), where the smallest achievable transmission ratio was found to be 0,81. This ratio of 0,81 will be tested at a speed of 30 km/h to determine the energy consumed during a 10-minute test. The result of the electric motorcycle conversion energy consumption test revealed that with a transmission ratio of 0,81, tested at a speed of 30 km/h for 10 minutes, the energy consumed was 0,173 kWh. Key Words: Ratio Transmission, Energy Consumption, Electric Motorcycle Conversion.